2017
DOI: 10.1111/ecoj.12510
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Responses to Immigration: Evidence from Internal Migration Driven by Weather Shocks

Abstract: We study the labour market impact of internal migration in Indonesia by instrumenting migrant flows with rainfall shocks at the origin area. Estimates reveal that a one percentage point increase in the share of migrants decreases income by 0.97% and reduces employment by 0.24 percentage points. These effects are different across sectors: employment reductions are concentrated in the formal sector, while income reduction occurs in the informal sector. Negative consequences are most pronounced for low‐skilled na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 21 publications
(47 reference statements)
9
82
4
Order By: Relevance
“…Studies investigating the impact of internal migration on local labour markets found negative effects of migration on wages and employment of residents at destinations (Boustan et al 2010;Kleemans and Magruder 2017). This could lead to higher rates of crime committed by residents who lose their jobs or receive lower wages.…”
Section: Second-stage Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies investigating the impact of internal migration on local labour markets found negative effects of migration on wages and employment of residents at destinations (Boustan et al 2010;Kleemans and Magruder 2017). This could lead to higher rates of crime committed by residents who lose their jobs or receive lower wages.…”
Section: Second-stage Resultsmentioning
confidence: 99%
“…This is not very informative for the Brazilian case, because the informal labour market is very large. Kleemans and Magruder (2017) document that in a developing country with a large informal sector, the impact of rural to urban migration is different for formal and informal sector workers.…”
Section: Second-stage Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taraz (2018) concludes that Indian farmers can adapt to moderately hot temperatures, but not to episodes of extreme heat. Finally, the results of a number of studies suggest that climate change may affect labor supply in developing countries, due to migration (Cattaneo and Peri, 2016;Henderson et al, 2017;Jessoe et al, 2018;Kleemans and Magruder, 2018), human capital accumulation (Garg et al, 2020), and sectoral mobility (Colmer, 2018;Chaijaroen, 2019). Lobell et al, 2011;Knox et al, 2012;Challinor et al, 2014;Chen et al, 2016), some focusing specifically on India (Guiteras, 2009;Burgess et al, 2017;Hari et al, 2018;Taraz, 2018).…”
Section: Introductionmentioning
confidence: 99%